Beginning Applescript - Kochan, Stephen G. (Wrox beginning guides., 2005)
Exercises; Chapter 7: Working with Files; Path Names: Traditional Mac and POSIX-style; What's in a Name?; The file Class; File Name Aliases; Reading and Writing Files; Enumerating Disks and Folders; Summary; Exercises; Chapter 8: Handlers; Writing a Handler; Passing Parameters to Handlers; Returning Handler Results; Argument Types; Local Variables; Call by Value; Recursive Handlers; Local/Global Variables and Variable Scope; Saving and Loading Handlers; Labeled Parameters; Specifying Patterns for Parameters; Summary; Exercises; Chapter 9: Error Handling; Beeps and Dialogs